2014
DOI: 10.1186/1471-2458-14-289
|View full text |Cite
|
Sign up to set email alerts
|

Empirical treatment for TB in HIV: lessons from a cohort study of people living with HIV treated in Recife, Brazil

Abstract: BackgroundTuberculosis (TB) is the leading cause of death related to HIV worldwide. This study analyzes the survival of People Living with HIV (PLHIV) reporting cough without bacteriological confirmation of TB and identify factors associated with death.MethodsProspective cohort with a consecutive sample of PLHIV, aged ≥ 18 years. Patient inclusion criteria were complaint of current cough of any duration at the time of the first study interview or during their subsequent routine visits to health services and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…We did not find a significant difference in the adjusted hazard for death between those treated for TB with any bacteriologic test (positive or negative) versus no test results in the secondary analysis. This finding is consistent with a study in Brazil which found no difference in mortality risk between PLWH who did or did not undergo TB bacteriologic testing [17]. This argues against the notion that the presence of TB bacteriologic testing is a marker of better-resourced sites (and therefore reduced mortality), as patients with a bacteriologic test would have been expected to have a lower mortality than those who were not tested if that were the case.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We did not find a significant difference in the adjusted hazard for death between those treated for TB with any bacteriologic test (positive or negative) versus no test results in the secondary analysis. This finding is consistent with a study in Brazil which found no difference in mortality risk between PLWH who did or did not undergo TB bacteriologic testing [17]. This argues against the notion that the presence of TB bacteriologic testing is a marker of better-resourced sites (and therefore reduced mortality), as patients with a bacteriologic test would have been expected to have a lower mortality than those who were not tested if that were the case.…”
Section: Discussionsupporting
confidence: 88%
“…Patients may not be able to produce a sputum sample for bacteriologic testing or access TB testing sites (e.g. for serial sputum collection) due to the distance or cost of transport [8, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies to investigate outcomes with empiric TB treatment as well as the Determine TB LAM test and treat strategies are on-going in sub-Saharan Africa [39] . One observational study from Brazil showed increased mortality with empiric TB treatment, although no weighted adjustment for selection bias was performed in this study [40] .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that severity of clinical condition may influence clinicians’ decision to treat empirically. In Brazil, HIV-positive patients with cough who were smear and culture negative and received TB treatment had a higher mortality than those who did not [29]. The authors interpreted that even after adjustment, severe HIV disease remained a confounder of the association between empirical TB treatment and mortality.…”
Section: Discussionmentioning
confidence: 99%